Tourist Shopping Trends: A Bibliometric Study of Influential Literature and Leading Scholars (1957-2024) - Sulistyowati, Tussi; Nisak, Solihatun; Mujanah, Siti; Halik, Abdul (PT. Riset Press International, 2025)
This research employed bibliometric analysis to explore the evolving interest in tourist shopping and its influence on tourist behaviour. It utilized Publish or Perish software to examine publication, author, and journal communication patterns within the Scopus database. An initial keyword search for